Proteomic comparison of four Eimeria tenella life-cycle stages: unsporulated oocyst, sporulated oocyst, sporozoite and second-generation merozoite. - Lal, K; Bromley, E; Oakes, R; Prieto, J; Sanderson, S; Kurian, D; Hunt, L; Yates, JR; Wastling, J; Sinden, R; Tomley, F (2009)
We report the proteomes of four life-cycle stages of the Apicomplexan parasite Eimeria tenella. A total of 1868 proteins were identified, with 630, 699, 845 and 1532 found in early oocysts (unsporulated), late oocysts (sporulated), sporozoites and second-generation merozoites, respectively. A multidimensional protein identification technology shotgun approach identified 812 sporozoites, 1528 merozoites and all of the oocyst proteins, whereas 2-D gel proteomics identified 230 sporozoites and 98 merozoite proteins. Comparing the invasive stages, we find moving junction components RON2 in both, whereas AMA-1 and RON4 are found only in merozoites and AMA-2 and RON5 are only found in sporozoites, suggesting stage-specific moving junction proteins. During early oocyst to sporozoite development, refractile body and most "glideosome" proteins are found throughout, whereas microneme and most rhoptry proteins are only found after sporulation. Quantitative analysis indicates glycolysis and gluconeogenesis are the most abundant metabolic groups detected in all stages. The mannitol cycle "off shoot" of glycolysis was not detected in merozoites but was well represented in the other stages. However, in merozoites we find more protein associated with oxidative phosphorylation, suggesting a metabolic shift mobilising greater energy production. We find a greater abundance of protein linked to transcription, protein synthesis and cell cycle in merozoites than in sporozoites, which may be residual protein from the preceding massive replication during schizogony.